1997
DOI: 10.1088/0953-4075/30/20/023
|View full text |Cite
|
Sign up to set email alerts
|

Low-energy electron attachment to fullerenes and in the gas phase

Abstract: We have investigated the low-energy (0-10 eV) electron attachment on C 60 and C 70 , using an improved energy resolution close to zero incident energy (0.030-0.060 eV). We have found evidence of a zero-energy attachment process (within 0.030 eV), for both C 60 and C 70 , indicating that a s-wave capture process is present at low energy for these two molecules. For C 60 , although in contrast with symmetry arguments, and with previous free-electron attachment experiments, this result is in full agreement with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 14 publications
4
57
2
Order By: Relevance
“…A combined fit to these n-dependent RET data and to the free electron data of Elhamidi et al (1997) yielded c ¼ 0.1 and " ¼ 0.1-0.2 (Fabrikant and Hotop, 2001). The s-wave zero energy peak dominates the cross-section only at very low energies (below 3 meV).…”
Section: B4 Electron Attachment To C 60mentioning
confidence: 95%
See 1 more Smart Citation
“…A combined fit to these n-dependent RET data and to the free electron data of Elhamidi et al (1997) yielded c ¼ 0.1 and " ¼ 0.1-0.2 (Fabrikant and Hotop, 2001). The s-wave zero energy peak dominates the cross-section only at very low energies (below 3 meV).…”
Section: B4 Electron Attachment To C 60mentioning
confidence: 95%
“…They exhibit a flat dependence of the attachment rate on the principal quantum number n of the Rydberg electron at high n, indicating an s-wave attachment process. In addition, more recent beam experiments (Elhamidi et al, 1997;Vasil'ev et al, 1997;Kasperovich et al, 2001) with free electrons have found evidence for a zero-energy attachment process (within about 0.03 eV). Several mechanisms for s-wave attachment involving formation of weakly bound (Weber et al, 1996) or virtual states of C À 60 , supported by the long-range polarization interaction, have been discussed.…”
Section: B4 Electron Attachment To C 60mentioning
confidence: 98%
“…Furthermore, in contrast with most other molecular systems, the measurements on C 60 found almost no resonant vibrational excitation in the gas phase. 11 Since the experimental findings suggest the occurrence of several metastable intermediates, and since the overall symmetry of C 60 is both interesting and intricate, it is useful to analyze the symmetries of the metastable states in terms of the irreducible representation ͑IR͒ of the icosahedral point group, I h , to which the C 60 molecule belongs. We have already examined the experimental angular distributions available thus far and have associated their features to our com-puted elastic differential cross sections over a broad range of collision energies.…”
Section: Introductionmentioning
confidence: 99%
“…The collision-induced electron transfer technique used in this work allows us to perform the study of negative fragmentation of the fullerene anion, which cannot be observed through electron attachment techniques. 5 …”
Section: Discussionmentioning
confidence: 99%